THE MOST COMMON REGISTERED COMORBIDITY IN WOMEN ADDICTED TO ALCOHOL - Milošević, Slađana V; Mihajlović, Sanja; Arsić, Nikola (PONS - medicinski časopis, 2022)
Objective: The main goal of the research is to determine comorbidities in women addicted to alcohol who were treated at the Clinic for Addiction Diseases of the Institute of Mental Health Belgrade. Methods: The research was conducted in January 2018, a retrospective study collected data for research purposes by reviewing available medical documentation - discharge lists. The research sample consists of 136 women addicted to alcohol between the ages of 18 and 68 who were treated at the Clinic for Addiction Diseases in the period from 2007 to 2017. For the needs of the research, and starting from the research variables, a special matrix for content analysis was made and filled in for each patient included in the research sample. Results: Among alcohol addicts, 17.6% had depression as comorbidity, and 5.9% had suicidal ideations. and 11.8% anxiety disorder. Conclusion: The study of comorbidities has significant implications, primarily due to the possible modification of the treatment of the underlying disorder and the adjustment of the therapeutic procedure to the comorbid disorder. Accordingly, timely diagnosis and treatment of comorbid diseases affects the easier course and better prognosis of the underlying disease on the one hand, but also reduces the cost of treatment and relieves the burden on the health system, on the other hand.